PENGARUH KINERJA KEUANGAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN YANG DIMODERASI VARIABEL UKURAN PERUSAHAAN (Studi Empiris Perusahaan Sektor Perdagangan, Jasa dan Investasi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Annisa Dayanty; Widhy Setyowati (Magister Manajemen STIE Bank BPD Jateng, 2020)
The purpose of this research is to find empirical evidence about the effect of financial performance and capital structure on firm value and whether company size can moderate the influence of financial performance and capital structure on firm value. The sample in this research is the trading, service and investment companies which is listed on the Indonesia Stock Exchange (IDX) in period 2016-2018. The research sample are 33 companies using purposive sampling technique. The analysis methods of this research used multiple linear regression analysis and Moderated Regression Analysis (MRA) to test the moderating variables. The results showed that financial performance and firm size had a positive effect on firm value. Capital structure has a negative effect on firm value. And the firm size can not moderate the financial performance and capital structure of the firm's value..